Autoimmune hemolytic anemia mediated by IgG and IgA in a patient with ulcerative colitis - Rivera Barquero, Ángelo (2015)
Chronic ulcerative indeterminate colitis (CUCI) is characterized by inflammation that primarily affects the rectum and may extend continuously to the colon. Anemia is common in patients with CUCI because of bleeding and the chronicity of the disease. However, CUCI has an immunological component. CUCI decrease the immune tolerance, which can lead in some cases to autoimmune hemolytic anemia (AIHA) usually mediated by antibodies of the IgG type. The patient in this case presents an AIHA associated with CUCI mediated both IgG and IgA antibodies, so it is an extremely rare situation.